2021
DOI: 10.3390/cancers13184510
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB and Pancreatic Cancer; Chapter and Verse

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is one of the world’s most lethal cancers. An increase in occurrence, coupled with, presently limited treatment options, necessitates the pursuit of new therapeutic approaches. Many human cancers, including PDAC are initiated by unresolved inflammation. The transcription factor NF-κB coordinates many signals that drive cellular activation and proliferation during immunity but also those involved in inflammation and autophagy which may instigate tumorigenesis. It is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 324 publications
(569 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, bacterial ablation increased PD-1 expression on effector T cells [69]. The binding of micro-organism-associated molecular patterns to specific Toll-like receptors leads to the activation of NF-κB and MAPK pathways, key promoters of pancreatic-cancer oncogenesis [70][71][72].…”
Section: Microbiome and Microbiota In Pannetsmentioning
confidence: 99%
“…Furthermore, bacterial ablation increased PD-1 expression on effector T cells [69]. The binding of micro-organism-associated molecular patterns to specific Toll-like receptors leads to the activation of NF-κB and MAPK pathways, key promoters of pancreatic-cancer oncogenesis [70][71][72].…”
Section: Microbiome and Microbiota In Pannetsmentioning
confidence: 99%
“…We, and others, have shown that smac-mimetics function by instigating auto-ubiquitylation and proteasomal degradation of cIAP1 and cIAP2 ( 284 , 285 , 288 , 289 ), which in the presence of a stimulus such as TNF, chemotherapy or TLR ligand, results in the formation of a RIPK1/caspase-8 complex, followed by caspase-8 cleavage and the induction of tumor cell death ( 281 , 285 , 290 , 291 ). A number of smac-mimetic compounds have been developed and due to their limited anti-cancer activities when used as single agents are now being tested in combination with immunotherapy and/or chemotherapy ( 6 , 281 , 282 ). For example, a trial reported in 2020, using Debio 1143 in combination with chemo-radiotherapy was the first drug combination in more than three decades to significantly improve overall survival in high risk HNSCC (includes OSCC) patients (ClinicalTrials.gov NCT02022098) ( 237 ) and a phase III trial is currently recruiting (ClinicalTrials.gov NCT04459715) ( Table 1 ) .…”
Section: Therapeutic Potential Of Targeting the Cytokine And Jak-stat...mentioning
confidence: 99%
“…The term cytokine encompasses interleukins, chemokines, interferons and tumour necrosis factors and all bind to corresponding receptors to activate cellular signaling pathways, including two related and evolutionary conserved signature signaling entities, the Janus Kinases (JAK: a family of tyrosine kinases) and the Signal Transducer and Activator of Transcription (STAT) protein family, which together constitute the JAK-STAT signaling pathway and has been studied in great detail ( 1 5 ). Another well studied pathway activated by cytokines is the NF-κB pathway, a family of inducible transcription factors, required in both innate and adaptive immunity to rapidly activate cellular responses ( 6 , 7 ). Over 50 cytokines can signal through the JAK-STAT pathway, mediated by JAK-mediated phosphorylation, ultimately regulating a signaling cascade upstream of multiple cellular activities ( 8 13 ).…”
Section: Introduction-jak-stat Signaling Regulation and Associated Di...mentioning
confidence: 99%
“…Then, N‐terminal part of p100 that shows NF‐κB2 p52 translocates into the nucleus by binding to RelB (Cildir et al, 2016; Feige et al, 2018). More details about NF‐κB signaling can be found in recent reviews (Figure 1) (Espinosa & Marruecos, 2021; Gilmore, 2021; Silke & O'Reilly, 2021).…”
Section: Introductionmentioning
confidence: 99%